2021
DOI: 10.3390/ijms22126452
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Metabolite, Sodium Thiosulfate: Clinical Applications and Underlying Molecular Mechanisms

Abstract: Thiosulfate in the form of sodium thiosulfate (STS) is a major oxidation product of hydrogen sulfide (H2S), an endogenous signaling molecule and the third member of the gasotransmitter family. STS is currently used in the clinical treatment of acute cyanide poisoning, cisplatin toxicities in cancer therapy, and calciphylaxis in dialysis patients. Burgeoning evidence show that STS has antioxidant and anti-inflammatory properties, making it a potential therapeutic candidate molecule that can target multiple mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 101 publications
1
42
1
Order By: Relevance
“…Thiosulfate is one of the principal stable metabolites of H 2 S – it can be detected in the circulation, and it is excreted via the urine [ 407 , 408 ]. This metabolite is easier to quantify than exhaled H 2 S, but, once again, any disease that induces the upregulation of any of the H 2 S-producing enzymes would be expected to increase its levels.…”
Section: The Path To Clinical Translationmentioning
confidence: 99%
“…Thiosulfate is one of the principal stable metabolites of H 2 S – it can be detected in the circulation, and it is excreted via the urine [ 407 , 408 ]. This metabolite is easier to quantify than exhaled H 2 S, but, once again, any disease that induces the upregulation of any of the H 2 S-producing enzymes would be expected to increase its levels.…”
Section: The Path To Clinical Translationmentioning
confidence: 99%
“… 95 , 96 Of note, one donor of H2S, sodium thiosulfate, is currently used in the clinical treatment of calciphylaxis in dialysis patients and cisplatin toxicities in cancer therapy. 97 The safety and tolerability of sodium thiosulfate have also been demonstrated in patients with acute coronary syndrome (ClinicalTrials.gov identifier NCT03017963), representing a promising subject for further translational studies. Although the role of vitamin E (a traditional antioxidant) for kidney diseases is unlikely to help much, 98 , 99 a recent phase IIb randomized controlled trial found that 400 mg tocotrienol-rich vitamin E supplementation for 12 months could ameliorate the progression of diabetic kidney disease (assessed by serum creatinine and eGFR).…”
Section: Therapeutic Approaches That Target Chronic Hypoxia In Ckdmentioning
confidence: 99%
“…Along with its sulfide releasing properties it is a known antioxidant. Moreover, STS was shown to be organ-protective in rodent models of acute liver injury ( 2 ), endotoxemia ( 3 , 4 ), bacterial sepsis ( 3 , 5 , 6 ), and, in particular, ischemia/reperfusion (I/R) injury of the brain ( 7 ), heart ( 8 13 ), and the kidney ( 14 , 15 ). Organ protective properties had also been demonstrated in larger species, i.e., canine tourniquet-induced limb ischemia and myocardial infarction induced by ligation of the left anterior descending coronary ( 16 ).…”
Section: Introductionmentioning
confidence: 99%